Designing Immersive Interactive Experiences in Sports Venues: The Role of Emotional Engagement - Siqi Liu (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The advent of augmented reality (AR) and virtual reality (VR) technologies has revolutionized the design of commercial spaces, particularly in sports venues, where creating an immersive and emotionally engaging atmosphere has become essential. This paper explores the integration of these technologies from a psychological perspective, emphasizing their impact on enhancing the spectator’s experience through emotional and sensory engagement. The rise of the metaverse has introduced new dimensions in how experiences in sports environments are conceptualized, making immersive experiences a critical component of modern sports venue design. These experiences involve a dynamic interplay between emotional responses and the artistic expressions enabled by advanced technologies. The study examines how immersive content can be crafted to resonate with spectators’ emotions, facilitating a deep, meaningful interaction that blurs the boundaries between the real and the virtual. Key elements of immersive experience design in sports venues are analyzed, focusing on how such environments can effectively mobilize affective responses to enrich the spectator experience. The findings suggest that well-designed immersive experiences in sports settings enhance emotional engagement and contribute to a more profound appreciation of athletic performance and the overall event atmosphere.